Transmissibility of HIV, the causative agent of AIDS by blood and blood products - ., Gurtler (Journal of Postgraduate Medical Institute, 2011)
The human immune deficiency virus previously named lymphadenopathy associated virus (LAV) or human T lymphotropic virus type 3 (HTLV-3) is a retro virus which has been spreading around the world from 1978-1980. A large body of epidemiological and virological evidence implicates this virus as the causative agent of the acquired immunodfeciency syndrome (AIDS). It is unknown where this virus originated from but we have to be aware of the fact that it might be present everywhere. In the last three years a new variant of HIV 1 was found which is now named HIV 2. This virus includes the isolates HTLV-4 and LAV-2 present in several countries of West Africa. HIV 2 seems to be indistinguishable from the simiam T lymphotropic virus type 3 (STLV-3). Recently re named SIV-2 found in African green monkeys. The clinical course of HIV 2 infection seems to be more benign, but cases of full blown AIDS due to this virus has also occurred and people have died.